Examining the relationship between bank profitability and economic growth: Insights from Central and Eastern Europe - Filipos Ruxho; Fejzula Beha (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this research article is to investigate the impact of bank profitability on the economic growth of 16 Central and Eastern European countries over the period from 1999 to 2022. The study aims to determine whether higher bank profitability has a positive influence on economic growth, challenging the notion that low bank profitability hinders economic growth. Design/methodology/approach: Our study employs an extensive empirical analysis, utilizing a range of econometric methods. We explore the relationship between bank profitability and economic growth, taking into account various factors and control variables. This includes assessing the impact of bank profitability on economic growth by considering a diverse set of economic indicators and factors influencing the banking sector. Findings: Our research consistently reveals a statistically and economically significant positive relationship between bank profitability and economic growth. Specifically, a one percent increase in the return on assets of banks is associated with a notable increase in economic growth, falling within the range of 0.534 to 0.625 percentage points. These findings suggest that higher bank profitability contributes positively to the economic growth of the studied Central and Eastern European countries. Research limitations/implications: While this study provides valuable insights into the relationship between bank profitability and economic growth, it has certain limitations. Future research in this area could delve deeper into the nuanced relationships between different dimensions of bank profitability and economic performance. Additionally, further investigations could explore the effects of varying ownership structures and competition dynamics on economic growth in these countries. This acknowledges the need for more in-depth research and understanding of the complex interplay between bank profitability and economic growth. Originality/value: This research contributes to the existing literature by shedding light on the positive impact of bank profitability on economic growth in Central and Eastern European countries. The findings offer valuable insights for policymakers, financial institutions, and researchers interested in understanding the dynamics between the banking sector and economic development in this region. The study's originality lies in challenging conventional wisdom and highlighting the potentially positive role of bank profitability in economic growth, thereby providing practical and policy-relevant implications.
Keywords: 650; Bank profitability; Economic growth; Central and Eastern Europe; Panel analysis